Synthesis and Optical Properties of meso‐CF3‐BODIPY with Acylethynyl Substituents in the 3‐Position of the Indacene Core. Issue 10 (30th August 2016) - Tomilin, Denis N.; Petrushenko, Konstantin B.; Sobenina, Lyubov N.; Gotsko, Maxim D.; Ushakov, Igor A.; Skitnevskaya, Anna D.; Trofimov, Alexander B.; A.Trofimov, Boris
Abstract: A strategy for the synthesis of asymmetric meso ‐CF3 substituted BODIPY (boron‐dipyrromethene) dyes bearing acylethynyl substituents at the 3‐position has been developed. The key step is the solid‐phase mechanoactivated ethynylation of meso ‐CF3 ‐dipyrromethanes by acylbromoacetylenes in Al2 O3 or K2 CO3 media. Additional possibilities for building up new aromatic heterocycles on the dipyrromethane systems has been demonstrated through the example of the pyrazole cycle "click‐assembly" over the benzoyl ethynyl moiety. The synthesized dyes fluoresce in a long wavelength region (628–663 nm) with high quantum yield (0.79–0.93). Abstract : Mechanoactivated BODIPY synthesis : BODIPY chromophores, combining a meso ‐CF3 group and acylethynyl substituents in one molecule, were synthesized for the first time. The key step is the solid‐phase mechanoactivated ethynylation of meso ‐CF3 ‐dipyrromethanes by acylbromoacetylenes in Al2 O3 or K2 CO3 media.